Optimalisasi Pemanfaatan Lahan Pekarangan Rumah dengan Tanaman Rempah pada Masa Pandemi Covid-19 - Ahmad Zaenal Arifin; Kuntum Febriyantiningrum; Nia Nurfitria (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
This community service program aims to provide additional knowledge and understanding in optimally utilizing home yards to increase community productivity while implementing government policies to stay at home during the Covid-19 pandemic.. Like rural communities in general, the people of Pongpongan village have quite large yards, but this is still not being utilized optimally. To provide additional knowledge and understanding regarding the use of homestead land, the initial stage of this program is to conduct socialization, then follow it up with training in planting and caring for good spices and then proceed to the monitoring process. The method used was to carry out focus group discussions and planting practices. Monitoring activities were carried out for approximately 3 months to determine the progress and obstacles faced by program participants. The results obtained indicate that many people have not used their yards and are constrained by capital. In addition, of all the participants who have yards that can still be used, they are interested in joining the follow-up program. This is because 100% of participants are satisfied and 85% of participants do not experience difficulties in running the programs given.